2020
DOI: 10.3389/fchem.2020.00023
|View full text |Cite
|
Sign up to set email alerts
|

Operando X-Ray Spectroscopic Techniques: A Focus on Hydrogen and Oxygen Evolution Reactions

Abstract: The study of structural as well as chemical properties of an electrocatalyst in its reaction environment is a challenge in electrocatalysis. This is very important for the better understanding of the dynamic changes in the reactivity with respect to the structure of catalysts to give insight into the reaction mechanism. The in situ/operando investigation of electrode/electrolyte interface has been increasingly explored in recent days due to the significant developments in technology. The review focus on operan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 110 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…The structural properties of in situ-formed species on a catalyst surface mainly determine the final catalytic behavior related to the local electronic structure of the species, such as hydrophilicity, co-ordination, and metal-oxygen covalency [ 55 , 80 ]. Recently, a series of sophisticated in situ/operando characterizations have led to the monitoring of the dynamic structural reconstructions of various types of electrocatalysts [ 61 , 63 , 81 , 82 ]. These efforts found that typical in situ-formed species on catalyst surfaces are metal oxyhydroxides [ 53 , 62 , 78 , 79 , 82 , 83 , 84 ].…”
Section: Fundamental Understanding Of Surface Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations
“…The structural properties of in situ-formed species on a catalyst surface mainly determine the final catalytic behavior related to the local electronic structure of the species, such as hydrophilicity, co-ordination, and metal-oxygen covalency [ 55 , 80 ]. Recently, a series of sophisticated in situ/operando characterizations have led to the monitoring of the dynamic structural reconstructions of various types of electrocatalysts [ 61 , 63 , 81 , 82 ]. These efforts found that typical in situ-formed species on catalyst surfaces are metal oxyhydroxides [ 53 , 62 , 78 , 79 , 82 , 83 , 84 ].…”
Section: Fundamental Understanding Of Surface Reconstructionmentioning
confidence: 99%
“…Generally, it is difficult to capture intermediates with a short lifetime, or to observe dynamic changes by ex situ characterization approaches. To track the surface change during an electrochemical reaction, in situ/operando techniques, specifically in situ/operando XRD/XPS/TEM/XAS/Raman methods, are the most powerful tools [ 61 , 63 , 82 , 94 , 138 , 139 ]. For example, in situ XAS can provide informative data regarding dynamic changes of the valence state, coordination number, and bond length [ 72 , 81 , 94 , 140 ].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
See 2 more Smart Citations
“…An emerging approach is to develop and use in situ techniques to elucidate decomposition pathways, including spectroelectrochemistry 59 and X-ray techniques. 60,61 Analysis of the products is required for determination of the faradaic efficiency and identification of any side reactions because a photocurrent can be generated from oxidative decomposition of the catalyst or electrode surface rather than representing true catalytic turnovers. GC-MS and UV−vis methods can be used to characterize solution species that indicate possible surface detachment.…”
mentioning
confidence: 99%